The gendered pains of life imprisonment - Crewe, Ben (The British journal of criminology, 2015)
As many scholars have noted, women remain peripheral in most analyses of the practices and effects of imprisonment. This article aims to redress this pattern by comparing the problems of long-term confinement as experienced by male and female prisoners, and then detailing the most significant and distinctive problems reported by the latter. It begins by reporting data that illustrate that the women report an acutely more painful experience than their male counterparts. It then focuses on the issues that were of particular salience to the women: loss of contact with family members; power, autonomy and control; psychological well-being and mental health; and matters of trust, privacy and intimacy. The article concludes that understanding how women experience long sentences is not possible without grasping the multiplicity of abuse that the great majority have experienced in the community, or without recognizing their emotional commitments and biographies.